2012
DOI: 10.3928/1081597x-20120921-02
|View full text |Cite
|
Sign up to set email alerts
|

Flap-off Epi-LASIK Versus Automated Epithelial Brush in PRK: A Prospective Comparison Study of Pain and Reepithelialization Times

Abstract: The flap-off group showed a statistically but not clinically significant advantage over the brush group in pain scores. However, no difference was noted in the percentage rate of epithelial healing time between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…12 Another technique is the use of epikeratome for epithelial removal and replacement after excimer treatment (epi on LASEK); however, the speed of wound healing was not much different from previously described techniques. 13 There are two methods of TransPRK: (1) two-step laser ablation which removes epithelium by phototherapeutic keratectomy (PTK) followed by the PRK for refractive correction and (2) single-step laser ablation where both the epithelium and stroma are ablated simultaneously. 14 Two laser platforms that can perform single-step TransPRK are SmartSurfACE (SCHWIND eye-techsolutions) and Streamlight (WaveLight Allegretto Wave Eye-Q Laser; Alcon Laboratories).…”
Section: Introductionmentioning
confidence: 99%
“…12 Another technique is the use of epikeratome for epithelial removal and replacement after excimer treatment (epi on LASEK); however, the speed of wound healing was not much different from previously described techniques. 13 There are two methods of TransPRK: (1) two-step laser ablation which removes epithelium by phototherapeutic keratectomy (PTK) followed by the PRK for refractive correction and (2) single-step laser ablation where both the epithelium and stroma are ablated simultaneously. 14 Two laser platforms that can perform single-step TransPRK are SmartSurfACE (SCHWIND eye-techsolutions) and Streamlight (WaveLight Allegretto Wave Eye-Q Laser; Alcon Laboratories).…”
Section: Introductionmentioning
confidence: 99%
“…The mean time of epithelial healing was 6.16 ± 1.7 (3–14) days in the chilled and 6.10 ± 1.59 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 days in the room temperature group with no statistically difference between the two groups (p = 0.32). The mean BCVA one month after PRK were 0.013 ± 0.03 (0–0.22) logMAR and 0.014 ± 0.03 (0–0.22) logMAR in the chilled and room temperature groups, respectively, with no statistically significant difference between the groups (P = 0.84) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 90%
“…The main cause of pain after PRK is baring of the corneal nerve after epithelial debridement, and it remains until epithelial repair occurs. For decreasing pain after PRK, various medical and surgical methods were suggested including: using bandage contact lens (BCL), dilute-tetracaine eye drops, 1 non-steroidal anti-inflammatory drugs (NSAIDs), 2 , 3 homatropine eye drops, 4 topical morphine, 5 transepithelial all surface laser ablation, 6 flap-off EPI-LASIK, 7 and LASEK. 8 …”
Section: Introductionmentioning
confidence: 99%
“…They found that epi-LASIK and PRK had similar amounts of pain on postoperative day 1 with 19 of 20 (95%) patients reporting pain in both eyes, but patients that underwent epi-LASIK demonstrated statistically more pain than PRK patients on days 3 and 6. 23 Similarly, Magone et al 24 found that flap-off epi-LASIK led to significantly less postoperative pain on days 1, 2, 3, and 4 when compared with automated epithelial brush PRK.…”
Section: ' Introductionmentioning
confidence: 96%